ANALYTICAL BASIS OF INVESTMENT PROCEDURES IN UZBEKISTAN AND THEIR TENDENCIES OF DEVELOPMENT - Sattorkulov, Obidkul Turdikulovich; Boboevich, 2Mukhametov Abubak; Kudratullaevna, Allayarova Mastura; Oktamovna, Bemukhammedova Barno; Vaxobjonovna, Mamajonova Saida; Abdulazizovich, Abduvokhidov Akmal; Khusanovich, Makhmudov Sherali; Islam, Abdugapparov (International Journal of Psychosocial Rehabilitation, 2020)
In the context of globalization, the country is trying to make the most of its opportunities and benefits in a competitive struggle for foreign capital, which is attracted primarily by the global markets. Systematic work carried out in our country in recent years to create a favorable investment and business climate, open access to foreign investment, ensuring legislative stability, development of small business and private entrepreneurship, thorough improvement of the investment climate is the basis for the growth of investment in our economy. As the President of the Republic of Uzbekistan Sh.M. Mirziyoev noted: “We need to take measures to fully realize the investment potential of our country in order to attract foreign investments. If we can formulate investment projects by region and industry for investors who want to invest in our economy, we can achieve a positive result.